Report for the period July 2009 - Dec 2009 : (labour) (CCS [Georgetown]GY, 2010)
Highlights the Directorate's activities in the field of labour during the period indicated.
Prepared for the Hon. Rooseveldt Skerrit...n preparation for the Twenty-First Inter-Sessional Meeting of the Conference of Heads of Government, Dominica, 11-12 March, 2010